ADAPTIVE HR: BALANCING TECHNOLOGY AND HUMANITY IN WORKFORCE MANAGEMENT - Adi Robith Setiana; Desy Tri Anggarini; Wasilatun Nikmah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study examines the impact of humanistic approaches in human resources and the use of technology on work force management performance at GoTo (Gojek-Tokopedia) Padang, with adaptability serving as a mediating variable. Using a quantitative research design, the study collected data from a sample of 100 employees selected through random sampling. The research employed structural equation modeling (SEM) using Smart PLS to analyze relationships among variables. Results indicate that while humanistic approaches do not directly impact workforce management performance, they positively influence adaptability, which then significantly improves workforce performance. The use of technology demonstrates both direct and indirect positive effects on workforce management performance, underscoring technology’s dual role in enhancing operational efficiency and adaptability. The findings suggest that GoTo’s human resource strategy should integrate human-centered policies and technological innovation to foster an adaptable workforce, which is crucial for achieving optimal performance outcomes in a dynamic, digital ecosystem. This research contributes to the understanding of strategic human resource practices in digital environments and highlights adaptability as a key factor linking employee-centered approaches and technological advancement to workforce success.